HUBUNGAN HIGIENITAS PRIBADISISWA-SISWI SEKOLAH DASAR DENGAN INFEKSI KECACINGAN - IRFAN DARFIKA LUBIS (LP2MTBM MAKARIOZ, 2019)
Background: Worm infections (STH infections) especially those transmitted through land (Soil Transmitted Helminths) still cause problems for public health with a high prevalence in the tropics especially in Indonesia. This infection generally attacks elementary school age children.Objective: This study aims to determine the relationship of Personal Hygiene of Elementary School (SD) students with the incidence of helminthiasis (STH infection) in students grade IV, V, VI of An Nizam Elementary School (SD), Medan Denai District.Methodology: This research is analytic descriptive with Cross Sectional approach. The sampling technique is done by the total sampling method with a total sample of 126 students. Data processed with Chi Square test.Research Results: The results showed that there was a relationship between the Personal Hygiene of Elementary School Students with the incidence of helminthiasis in An Nizam Elementary School, Medan Denai District. The incidence of helminthiasis (STH infection) in An Nizam Elementary School, Medan Denai District is 7.9%.Conclusion: There is a relationship between the personal hygiene of elementary school students with the incidence of helminthiasis (STH infection) in grade IV, V, VI students at An Nizam Elementary School, Medan Denai District